Assessing the role of tax-benefit systems in reducing the gender income gap in Latin America - María Cecilia Deza; Mariana Dondo; H. Xavier Jara; David Rodriguez; Javier Torres (Inter-American Development Bank (IDB), 2025)
This paper aims to assess the extent to which cash transfers, direct taxes, and social contributions help to reduce gender income inequalities in seven Latin American countries: Argentina, Bolivia, Colombia, Ecuador, Mexico, Peru, and Uruguay. We apply microsimulation techniques to household survey data and allocate incomes within the household, assuming that each person retains the income they receive (e.g., earnings, benefits targeting mothers) and pays taxes and social insurance contributions on an individual basis according to each countrys rules. Then, we compare gender income ratios based on market (before taxes and benefits) and disposable (after taxes and benefits) income. Our results show that, at the bottom of the distribution, tax-benefit systems significantly reduce gender income disparities in most countries due to the effect of social assistance benefits received by mothers in poor households. Additionally, we find that women have substantially higher poverty rates than men based on individual disposable income. Gender differences in poverty fade away when income is pooled at the couple level and, even more so, at the household level.
Keywords: D31; J16; J7; H24; I32; I38; 330; Taxes; Benefits; Microsimulation; Gender gap; Latin America